2020
DOI: 10.1186/s12877-020-01533-8
|View full text |Cite
|
Sign up to set email alerts
|

Fear of falling and cognitive impairment in elderly with different social support levels: findings from a community survey in Central Vietnam

Abstract: Background: Fear of falling (FoF) in the elderly is one of the major public health concerns in this era of aging of the population. As there is limited evidence on how cognitive function may differ by social support level in relation to FoF among the elderly, this cross-sectional study aims to investigate the prevalence of FoF and the associations between cognitive impairment and FoF by the social support level, after adjustments for potential confounders. Methods: Data from the "Health needs assessment of eld… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 35 publications
0
24
1
Order By: Relevance
“…This may be due to women generating more chronic diseases, musculoskeletal problems, as well as anatomical and biopsychological gender differences [28]. Besides, according to other studies, aging is significantly associated with increased fear of falling [12,29]. Considering the longer life expectancy of older women than men, the high fear of falling in older women can be justified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to women generating more chronic diseases, musculoskeletal problems, as well as anatomical and biopsychological gender differences [28]. Besides, according to other studies, aging is significantly associated with increased fear of falling [12,29]. Considering the longer life expectancy of older women than men, the high fear of falling in older women can be justified.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the difference in the level of fear of falling of elderly living in urban and rural regions could be attributed to differences in their lifestyle as well as the quality of life [30]. Due to the integrity of individuals' culture in rural areas, older people receive higher social support from family, neighbors, or friends, i.e., effective in improving their wellbeing and physical health, resulting in better cognitive function and mental wellbeing; consequently, such conditions reduce fear of falling in the elderly living in villages [12]. Arruda addressed no difference in the risk of falls between urban-and rural-living elderly [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FOF is associated with frailty, sarcopenia, and impaired cognitive function. 16,[20][21][22] Maintenance of daily physical activity prevents anxiety, including FOF, and prevents deterioration of physical function. 23 Therefore, maintaining physical activity and psychological care is important for preventing frailty syndrome and disease onset due to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…One of the predominant features of dementia is deterioration in undertaking activities of daily life (ADL), which is reflected in aspects of physical limitation and cognitive deficiency (Gélinas et al, 1999). These might also impede patients' capacity to participant in exercise, potentially increasing their risk of falling and exacerbating caregivers' fear for their exercise safety (Cedervall et al, 2015;Stubbs et al, 2014;van Alphen et al, 2016b;Vo et al, 2020). However, previous studies showed inconsistent results about the effect of the capacity to undertake ADL on the level of PA (Stubbs et al, 2014).…”
Section: Introductionmentioning
confidence: 99%